Effects of multicomponent exercise injury prevention programs on adolescent team athletes (10–19 years old): a systematic review and meta-analysis - Liu, Honghao; Liu, Xiaoming; Yin, Long (Frontiers in Pediatrics, 2026)
ObjectiveThe aim of this study was to assess the efficacy of multicomponent exercise injury prevention programs in adolescent team athletes and to determine the optimal training programs characteristics, including program duration and potential sex-related differences, through subgroup analysis.MethodsA thorough literature search was conducted in PubMed, Web of Science, Embase, EBSCOhost, and the Cochrane Library, covering all publications from their inception to 20 July 2024.ResultsThis meta-analysis of 16 randomized controlled trials evaluated the effectiveness of multicomponent exercise interventions in reducing sports-related injuries among adolescent team athletes and identified optimal training components, duration, and potential sex-related differences. The results revealed that these programs significantly reduced injuries across various body regions: total injuries by 35% [incidence rate ratio (IRR) = 0.65, 95% confidence interval (CI): 0.54–0.77], lower-extremity injuries by 33% (IRR = 0.67, 95% CI: 0.57–0.80), knee injuries by 22% (IRR = 0.78, 95% CI: 0.66–0.92), ankle injuries by 38% (IRR = 0.62, 95% CI: 0.47–0.81), and upper-extremity injuries by 32% (IRR = 0.68, 95% CI: 0.40–1.17). These programs also reduced acute injuries by 32% (IRR = 0.68, 95% CI: 0.57–0.81) and overuse injuries by 39% (IRR = 0.61, 95% CI: 0.49–0.76). Findings suggest that interventions under 20 min (IRR = 0.59, 95% CI: 0.44–0.79) and incorporating warm-up, jumping/plyometric, strength, agility, and balance are most effective (IRR = 0.55, 95% CI: 0.41–0.73). Subgroup analyses revealed stronger effects in females (IRR = 0.56, 95% CI: 0.35–0.88) than in males (IRR = 0.66, 95% CI: 0.55–0.80) and found greater effectiveness in interventions lasting under 20 min compared to those lasting 20 min or more (IRR = 0.70, 95% CI: 0.57–0.86). Notably, most research training programs include balance and strength training.ConclusionMulticomponent sports intervention programs are effective in reducing injury incidence among adolescent team athletes. Subgroup analyses identified significant sex-related differences and confirmed the optimal training duration (<20 min) as well as the most effective training combination (warm-up, jumping/plyometric, strength, agility, and balance training). Strength training (focusing on the hamstrings and core) and balance training are recommended for inclusion in a multicomponent exercise injury prevention program. However, the low quality of current evidence underscores the need for rigorous studies to confirm these findings.Systematic Review RegistrationCRD42024580565.